A.M. Gorky аnd F.M. Dostoevsky: polemicism of their creativity (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the problem of the polemics on works of the greatest representatives of Russianliterature of the 19th and 20th centuries Alexey Maximovich Gorky and Fedor Mikhailovich Dostoevsky,which was studied by many literary scholars of the last century.The author of the article emphasizes that the polemic occurred between content and expressionplan, as a result of which one can perceive the form in abstraction from content, and content in abstracting from the form or even opposing them to each other.The article emphasizes the idea that in the creative consciousness of A. Gorky Fyodor Dostoevskyhas always visibly or invisibly attended since the 90s up to the «Life of KlimSamgin». The problem ofGorky and Dostoevsky is very important for understanding the ethical and aesthetic views of Gorky.The article proves the idea that works devoted to the problem of «Gorky and Dostoevsky» there isone feature common to most is Gorky’s rejection of Dostoevsky’s «social pedagogy», which was precisely defined, prompting in due time lively polemics the book by Yu. Kudryavtseva «ThreecirclesofDostoevsky.»